1997
DOI: 10.1002/(sici)1097-0142(19970101)79:1<3::aid-cncr2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and primary gastric lymphoma

Abstract: These results suggest that H. pylori is more likely to be associated with early states of primary gastric lymphoma than with advanced states. Thus, H. pylori may disappear during the progression of primary gastric lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 157 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…32 However, lar to those for the previously reported patients with in the current study, H. pylori was detected in all patients (Table 2), even though all 12 lymphomas masgastric adenocarcinoma without lymphoma. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…32 However, lar to those for the previously reported patients with in the current study, H. pylori was detected in all patients (Table 2), even though all 12 lymphomas masgastric adenocarcinoma without lymphoma. …”
Section: Discussionsupporting
confidence: 81%
“…14 - 21,32 with double primary gastric lymphoma and adenocarThe authors' previous study revealed H. pylori to be cinoma were 71% and 36%, respectively (80% and 40%, detected in only 50% of the gastric lymphomas invadrespectively, for early adenocarcinoma, and 0% and ing the deep portion of submucosa or even deeper, in 0%, respectively, for advanced adenocarcinoma), contrast to 90% of those restricted to the mucosa and which appeared to be slightly lower but relatively simithe superficial portion of the submucosa. 32 However, lar to those for the previously reported patients with in the current study, H. pylori was detected in all patients (Table 2), even though all 12 lymphomas masgastric adenocarcinoma without lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been implicated in gastric adenocarcinoma (6 -9) and gastric lymphoma (10), leading to its classification as a type I human carcinogen (11). H. pylori is a chronic pathogen, and the means by which this organism is able to persist in the stomach and resist or evade destruction by the immune system is central to its involvement in disease.…”
mentioning
confidence: 99%